The Effect of Compression Ratio on Pollutant Emission of a Diesel Engine Fuelled with Nano Diesel - Kathum Nassir, Abdulkhodor; A. K. Shahad, Haroun (International Journal of Engineering and Technology, 2018)
This studying aims to examine the impact of compression ratio (CR) on the pollutants of a compression ignition engine (CIE) fuelled with Nano-diesel. Nano-particles of Al2O3 and TiO2 are used as additives to diesel fuel with particle size less 45 nm. The impact is tested for 25, 50, 100 and 150 ppm doses. Tests are performed at different loads and a speed of 1500 rpm. Three CR are used namely13.5, 15.5 and 17.5. Results illustrated the affects of CR on the emissions of CO, CO2, NOx, smoke opacity and UHC. Results showed Â that CO concentration rises with increasing of CR for Al2O3. It is increased by 2.5, 4.9 and 15.3% for the three ratios at 100ppm and 25% load while at full load there is no much effect as a result of high combustion temperature. Negligible effect is noticed for TiO2.The concentration of CO2rises with increasing CR at all dozes but it is very clear with 150ppm and 25% load3.7, 4.1 and 4.8% for Al2O3. The effect ofÂ TiO2 is higher than that of Al2O3. The results also, show that NOx concentration is increased and becomes 604, 651 and 698ppm for 13.5, 15.5 and 17.5 respectively for Al2O3 at 25ppm and 25% load. The impact of Al2O3 is more noticeable than that of TiO2.The smoke opacity is slightly affected by CR for Al2O3 andÂ TiO2 at all doses and 25% load. UHC decreases slightly from 79, 75 and 71 ppm for CR of 13.5, 15.5 and 17.5 respectively for Al2O3 at 25ppm and 25% load. UHC decreases from 68, 65 and 61 ppm for CR13.5, 15.5 and 17 respectively for TiO2 at 25ppm and 25% load.Â Â